ARDL PANEL MODEL IN CONTROL OF EXCHANGE RATE SYSTEMS THROUGH POST-COVID-19 OPEN ECONOMY MODEL - Abdiyanto Abdiyanto; Ronald Farel Siahaan; Rusiadi Rusiadi; Ade Novalina; Bhaktiar Efendi; Lia Nazliaan Nasution; Suhendi Suhendi; Diwayana Putri Nasution (Proceeding of The International Conference on Economics and Business, 2022)
Destination from study this that is for test variable Interest Rates, Inflation , Total Money Supply and GDP how much big in take effect to EXCHANGE variable . And for knowing is panel level _ ethnic group interest , inflation , money supply , unemployment , investment , and GDP have an effect positive and significant to exchange rates in America, Australia, China, Canada , Indonesia, Japan , South Korea, Malaysia, Singapore, Russia and Thailand. Approach study this is study associative / quantitative with the Simultaneous model and the ARDL Panel where aim see linkages Among independent variables and dependent variables that spread panel in Top Major Exchange Rate countries in 11 APEC Countries. Study this conducted against 11 countries with exchange rate strongest in the APEC countries in the world (America, Australia, Malaysia, Singapore, South Korea, Japan , China, Indonesia, Canada , Russia , and Thailand). The ARDL Panel Analysis results show that the Leading Model Control indicators Exchange Rate System Through the Post -Covid-19 Open Economy Model, the Top Major Exchange Rates in Eleven Apec Countries (Varies) are JUB and GDP. this _ due to the results data processing , the ROE variable is variable that gives stable influence , ie _ effect on the inside period long nor period short in give influence significant to score exchange , which is assessed from level short run and long run stability in the table result .